A supramolecular vesicle of camptothecin for its water dispersion and controllable releasing. (30th January 2015) - Ma, Mingfang; Shang, Wenqing; Xing, Pengyao; Li, Shangyang; Chu, Xiaoxiao; Hao, Aiyou; Liu, Guangcun; Zhang, Yimeng
Abstract : Graphical abstract: Highlights: The supramolecular vesicles constructed by β-cyclodextrin with camptothecin are reported. The mechanism of the vesicle formation was studied by various methods. The effect of competitive guest 1-hydroxyadmantane on the vesicles was discussed. The antitumor activity of the camptothecin supramolecular vesicles on HeLa cells was studied in detail. Abstract: Camptothecin, as an antitumor drug, has shown significant antitumor activity against various cancers through the inhibition of topoisomerase I. However, its poor solubility severely limits the clinical applications. Here, we report a camptothecin supramolecular vesicle based on the host–guest interactions, which can uniformly disperse camptothecin into water and greatly enhance camptothecin aqueous solubility. The camptothecin vesicles were identified by transmission electron microscopy (TEM), scanning electron microscopy (SEM), and dynamic light scattering (DLS). X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), UV–vis spectrum, 1 H NMR and 2D NMR ROESY were further employed to study the formation mechanism of the vesicles. Furthermore, camptothecin could be controllably released when the competitive guests were added into the vesicles system. Finally, the camptothecin vesicles in aqueous solution exhibited comparable antitumor activity in vitro as natural camptothecin in DMSO to HeLa cells under the same conditions.